2005
DOI: 10.1111/j.1467-8624.2005.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Ego Development and Ethnic Identity Formation in Rural American Indian Adolescents

Abstract: Ethnic identity development was assessed in the context of ego development in 12- to 15-year-old students from a Southeastern American Indian community. Self-protective was the modal level and was characterized by awareness of ethnic group membership but little exploration or self-reflection. Impulsive adolescents had the least developed ethnic identities and highest levels of interpersonal vulnerability. Conformist adolescents expressed positive feelings about ethnic group affiliation, described relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…No other attempts to analyze cases in addition to group data were reported. Type differences were proposed in four articles (Bonanno et al 2005;Newman 2005;Poehlmann 2005;Troop-Gordon and Asher 2005). With one exception, only one of the seven differentiating characteristics could be found in each of the analyzed articles.…”
Section: Two Psychologies In the Pre-world War II Eramentioning
confidence: 95%
See 2 more Smart Citations
“…No other attempts to analyze cases in addition to group data were reported. Type differences were proposed in four articles (Bonanno et al 2005;Newman 2005;Poehlmann 2005;Troop-Gordon and Asher 2005). With one exception, only one of the seven differentiating characteristics could be found in each of the analyzed articles.…”
Section: Two Psychologies In the Pre-world War II Eramentioning
confidence: 95%
“…So, the articles were analyzed only in respect to the seven remaining characteristics. Qualitative description of data, in addition to quantitative data, was provided in two articles (Hansen and Markman 2005;Newman 2005). Attempt to discuss whole person and relationships was made in one article (Brown and Bigler 2005).…”
Section: Two Psychologies In the Pre-world War II Eramentioning
confidence: 99%
See 1 more Smart Citation
“…In their study of 379 ethnic minority adolescents from Grades 6 through 9, using the Multigroup Ethnic Identity Measure, they found growth in EI over time; also, minority adolescents with higher levels of EI reported better relationships with their parents than did those with lower levels of EI. In a study of 96 American Indian adolescents and their parents, Newman (2005) found that EI was associated with social competence but had no significant effect on self-esteem. Yasui and Dishion (2007) developed a conceptual framework of child and adolescent development using EI as a central construct.…”
Section: Introductionmentioning
confidence: 97%
“…An assumption that greater adjustment is associated with those who possess a bicultural identity has been found by some researchers (Moran et al, 1999;Oetting & Beauvais, 1990-1991Whitesell et al, 2006), but not others (Gotowiec, 2000;Jones & Galliher, 2007). Consistent with findings among other ethnic groups, higher adjustment has been shown among Native adolescents who score high on measures of ethnic identity (e.g., Jones & Galliher, 2007;Newman, 2005;Rieckmann, Wadsworth, & Deyhle, 2004).…”
Section: Research On Culture and Child And Adolescent Developmentmentioning
confidence: 78%